Management and prognosis of gastroschisis in a public maternity hospital in the state of Sergipe (Research, Society and Development, 2022)
Gastroschisis is the most common congenital anomaly of the abdominal wall, defined as a defect in its closure, resulting in evisceration of intra-abdominal structures. It often appears isolated, without association with other anomalies. In different regions of Brazil and the world, there has been an increase in the incidence of this pathology - currently between 2 and 5 per 10,000 live births - configuring a public health problem to be equated. The present study aimed to analyze the profile of births and deaths due to gastroschisis, to identify the causes of in-hospital mortality and the occurrences of postoperative complications of newborns with gastroschisis, in a public maternity hospital in the state of Sergipe. This is a prospective observational cohort study, aligned with the multicenter study 'PAEDSURG' in which all Brazilian hospitals would be eligible to participate. Data were collected between 11/15/2021 and 11/15/2022, from all consecutively eligible cases, under the supervision of the pediatric surgeon coordinating the research site, Drª Marcia Montalvão. Five cases of newborns with gastroschisis were described, all born by cesarean section, prematurity was seen in 4 cases (median GA 35 weeks), with low birth weight observed in 75% of cases (median 2180g). All mothers were primiparous, all had prenatal care and underwent an ultrasound examination, showing gastroschisis in 4 NBs, 3 mothers had low maternal age (median of 18 years), none with higher education. The mortality rate was low (of the 5 NBs, only 1 died) and socioeconomic factors were associated with the occurrence of gastroschisis.